Chuva e banco de sementes do solo em diferentes sistemas de restauração ecológica da floresta estacional semidecidual - Villota Cerón, Diana Elizabeth [UNESP] (2015)
The assessment of natural regeneration is important to understanding the successional trajectory of restored ecosystems and determining if the efforts to restore the stability and biological integrity are being effective. Seed availability is an important factor for the survival and persistence of plant community within the habitat. Thereby, seeds bank and seeds rain have been considered as the principal processes for plant communities maintenance. The aim of this study was to evaluate the role of the soil seed bank and the seed rain for the regeneration dynamics of plant communities under different seasonal semi-deciduous forest restoration systems. The study was undertaken in two experimental sites at Botucatu county (São Paulo), each one havind contrasting soil characteristics. Five restoration systems were stablished in 1997-1998, in a random block design with three replications in each site, with 50 x 50 m plots. Treatments were: a) direct seeding (SEMD), b) agroforestry system (SAF), c) timber and firewood mixed species plantation(COML), e) high-diversity plantation (PDIV) and f) passive restoration as control (RPSV). Furthermore, a natural forest fragment (FRAG) was evaluated in each area as a reference ecosystem. Soil samples were collected at 5 cm deepth (8 samples perplots), in order to analyse the seed bank by the germination method, respectively during the rainy and dry seasons. Soil samples were installed in germination boxes at the nursery. Sedling emergence was monitored during six months. For the seed rain study, 4 circular traps of 0.25 m² were installed in each plot, and the seeds were collected monthly during one year. The seed bank was composed mainly by herbaceous species in all restoration systems, comprinsing 83% and 73% of species for areas 1 and 2 respectively. The seed bank average density was 632.29 and 794.61 seeds / m², for areas 1 and 2, respectively. The highest dens ...